X-ray diffraction analysis of MTA-Plus, MTA-Angelus and DiaRoot BioAggregate - Guven, Yeliz (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: The purpose of this study was to investigate and compare the crystalline structures of recently released MTA Plus (MTA-P), MTA Angelus (MTA-A), DiaRoot BioAggregate (BA) by X-ray diffraction (XRD) analysis. MATERIALS AND METHODS: Phase analysis was carried out on powder and set forms of tested materials. The powder specimens placed into sample holders that were packed with a glass slide and the set samples prepared according to the manufacturer's instructions were placed into molds. The samples after being set for three days at 37°C and 100% humidity in an incubator were mounted onto the XRD machine and phase identification was accomplished using a search-match software program. RESULTS: XRD findings indicated that major constituents of MTA-P were bismuth oxide, portlandite, dicalcium silicate and tricalcium silicate. The crystal structure of MTA-A were similar to those of MTA-P except for the absence of portlandite. Additionally, MTA-A had tricalcium aluminate differing from MTA-P. BA mainly differed from MTA-P and MTA-A by the radiopacifier (tantalum oxide-TO) in its composition. CONCLUSIONS: The majority of constituents of the tested materials have shown similarity except for the presence of tricalcium aluminate in MTA-A and the inclusion of TO in BA. In addition, set MTA-P showed a strong peak of portlandite.